2011
DOI: 10.1208/s12249-011-9742-7
|View full text |Cite
|
Sign up to set email alerts
|

Microemulsion-Based Gel of Terbinafine for the Treatment of Onychomycosis: Optimization of Formulation Using D-Optimal Design

Abstract: Abstract. The aim of the present investigation was to evaluate microemulsion as a vehicle for dermal drug delivery and to develop microemulsion-based gel of terbinafine for the treatment of onychomycosis. Doptimal mixture experimental design was adopted to optimize the amount of oil (X 1 ), Smix (mixture of surfactant and cosurfactant; X 2 ) and water (X 3 ) in the microemulsion. The formulations were assessed for globule size (in nanometers; Y 1 ) and solubility of drug in microemulsion (in milligrams per mil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
62
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(64 citation statements)
references
References 34 publications
2
62
0
Order By: Relevance
“…Therefore, different models, viz., linear, quadratic, cubic, and special cubic, were first analyzed for the response variables (Y 1 to Y 3 ) by the predicted residual sum of square (PRESS) statistic for determination of suitability of model fitting. The PRESS statistic basically analyzes the prediction ability of the fitted models and the model with minimum value of PRESS statistic is usually considered as the most predictive model for the given set of data [16] . The quadratic model was selected for all three response variables as they observed the smallest value of PRESS statistic as compared to other three models (Table 6).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, different models, viz., linear, quadratic, cubic, and special cubic, were first analyzed for the response variables (Y 1 to Y 3 ) by the predicted residual sum of square (PRESS) statistic for determination of suitability of model fitting. The PRESS statistic basically analyzes the prediction ability of the fitted models and the model with minimum value of PRESS statistic is usually considered as the most predictive model for the given set of data [16] . The quadratic model was selected for all three response variables as they observed the smallest value of PRESS statistic as compared to other three models (Table 6).…”
Section: Resultsmentioning
confidence: 99%
“…An o/w microemulsion containing an experimental drug (NB-002) effectively delivered across the skin present nearby nail plate [14] . In another attempt itraconazole could be delivered in nail plate through a o/w microemulsion formulation applied on nail plate in an in vitro drug loading study [15] , other than this, microemulsion based gel of terbinafine showed better in vitro transdermal permeation compared to marketed formulation [16] .…”
mentioning
confidence: 99%
“…Three wells were made in the middle of the plates with the help of sterile cork-borer, each well (6 mm internal diameter) was accurately filled with either 0.1 ml of the nPEVs formula, 0.1 ml of the control formula or an amount of Dermofix Õ cream equivalent to the sertaconazole dose in the 0.1 ml nPEVs formula. The plates were then incubated at 25 C for three days in the incubator to allow fungal growth (Barot et al, 2012;Sahoo et al, 2014).…”
Section: Microbiological Efficacy Of Npevs For the Treatment Of Onychmentioning
confidence: 99%
“…It is a fungal infection that causes thickening, discoloration of the nail (Hall et al, 1997;Sigurgeirsson & Ghannoum, 2012;Barot et al, 2012). As infection progresses, the nail becomes brittle and starts to break or totally comes out of the toe or finger.…”
Section: Introductionmentioning
confidence: 99%
“…Three wells in Petri dishes containing different strains were bored, and 0.1 g of each formulation containing drug was filled. After the incubation period, anti-fungal activity was analysed by comparing the zone of inhibition [66]. Flores et al (2013) have evaluated anti-fungal efficacy of nanocapsules and nanoemulsions containing Melaleuca alternifolia (tea tree oil) using two different in vitro models of dermatophyte nail infection.…”
mentioning
confidence: 99%